Correction to the article “Viscoelastic Tests in the Evaluation of Haemostatic Disorders in SARS-CoV-2 Infection”, Published on Acta Med Port 2021 Jan;34(1):35-46. - de Sousa, Carla (2021)
On page 36, in the fifth sentence of right-side column, where it reads: ”Direct thrombin inhibitors (DTI) (argatroban, bivalirrubin) are used in COVID-19 infected patients with significantly lower antithrombin levels,24 or if heparin induced thrombocytopenia (HIT) occurs.”It should read: “Direct thrombin inhibitors (DTI) (argatroban, bivalirudin) are used in COVID-19 infected patients with significantly lower antithrombin levels,24 or if heparin induced thrombocytopenia (HIT) occurs.”Article published with errors: https://www.actamedicaportuguesa.com/revista/index.php/amp/article/view/14784